2014
DOI: 10.1007/s40273-014-0245-8
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of OnabotulinumtoxinA (BOTOX®) for the Management of Urinary Incontinence in Adults with Neurogenic Detrusor Overactivity: A UK Perspective

Abstract: ObjectivesTo evaluate the cost effectiveness of onabotulinumtoxinA (BOTOX®, 200 units [200 U]) for the management of urinary incontinence (UI) in adults with neurogenic detrusor overactivity (NDO) due to subcervical spinal cord injury or multiple sclerosis that is not adequately managed with anticholinergic drugs (ACHDs).PerspectiveUK National Health Service (NHS) perspective.MethodsA Markov state-transition model was developed, which compared onabotulinumtoxinA + best supportive care (BSC) with BSC alone (com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Hamid et al reported a total cost of $5,037 for BoNT-A treatment over 5 years, which amounted to $14,483 with addition of best supportive care. 14 The total estimated costs were notably higher in other studies, up to $35,300, likely due to a more comprehensive inclusion of supportive care as well as invasive treatments in estimation of costs accrued during the followup period.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…Hamid et al reported a total cost of $5,037 for BoNT-A treatment over 5 years, which amounted to $14,483 with addition of best supportive care. 14 The total estimated costs were notably higher in other studies, up to $35,300, likely due to a more comprehensive inclusion of supportive care as well as invasive treatments in estimation of costs accrued during the followup period.…”
Section: Resultsmentioning
confidence: 74%
“…13 Hamid et al estimated the costs of best supportive care, including a combination of behavioral therapy, incontinence pads, CIC, and the management of adverse events to be $11,683 in the United Kingdom over a 5-year period. 14 In a more recent study, Jaggi et al provided a thorough breakdown of the health care utilization related to neurogenic bladder in the United Kingdom, with a total average annual cost of $3,790. 15 In their study, the largest category of costs was related to hospitalization, with an average cost of $9,901 per year.…”
Section: Overview Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost-effectiveness has been studied between BoNTA with supportive care versus supportive care alone. It confirmed that BoNTA with supportive care is cost effective with 100 % probability [36].…”
Section: Botulinum Toxin a (Bonta)mentioning
confidence: 63%
“…Although the investigators found no difference in the reduction in incontinence episodes (−1.6 vs. −1.7), there was a significant difference in the number of patients reporting “cure” by the study criteria (27% vs. 13%, respectively, p=0.003). 18 One team of investigators found that onabotulinumtoxinA (BoNT-A) used to treat refractory neurogenic detrusor overactivity from SCI or MS was more effective than “best supportive care” alone, adding 0.4 Quality Adjusted Life years (QALY), at an increased cost of £1,689 over 5 years 19• . The authors felt this was cost effective, but leave the question unanswered regarding how much the system should be willing to pay for one additional QALY.…”
Section: Introductionmentioning
confidence: 99%